Identification of colupulone and lupulone as the main contributors to the antibacterial activity of hop extracts using activity-guided fractionation and metabolome analysis - Li, Yan; Dalabasmaz, Sevim; Gensberger-Reigl, Sabrina; Heymich, Marie-Louise; Krofta, Karel; Pischetsrieder, Monika (Food Research International, 2023)
Hop is widely used in beer brewing and as a medicinal product. The present study comprehensively analyzed the main molecular determinants of the antibacterial activity of hop extracts. Minimum inhibitory concentrations (MIC) against Bacillus subtilis between 31.25 and 250 µg/mL were found in the ethanolic extracts of five hop varieties for beer brewing, but not in the tea hop sample. Activity-guided fractionation revealed the highest antibacterial activity for lupulone and adlupulone (MIC 0.98 µg/mL). Metabolome profiling and subsequent multistep statistical analysis detected 33 metabolites out of 1826 features to be associated with the antibacterial activity including humulone, adhumulone, colupulone, lupulone, and adlupulone. Xanthohumol, the three humulone- and three lupulone congeners were quantified in the hop extracts by a validated ultrahigh-performance liquid chromatography–mass spectrometry method. Considering concentrations and MICs, colupulone and lupulone were identified as major contributors to the antibacterial activity of hop extract with the highest antibacterial activity values (concentration/MIC) of 1.59 and 2.56.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Antibacterial activity; Hop; Humulone; Humulus lupulus; Lupulone; Metabolome; Quantification